Valorization of textile waste: non-woven structures and composites - Alves, Diana I.; Barreiros, Mariana; Fangueiro, Raúl; Ferreira, Diana P. (Frontiers in Environmental Science, 2024)
Each year, millions of tons of clothing are both produced and discarded, exerting a substantial impact on the environment and public health. Even when textile waste is disposed of in landfills, it persistently adds to pollution in the air, water, and soil. This review explores the diverse implications of textile waste, examining circular economy principles and highlighting opportunities for transforming textile waste into eco-friendly materials. This review highlights opportunities to repurpose textile waste into new products, aligning with the principles of a circular economy. The discussed materials, such as cotton, wool, polyester, nylon, and kevlar, can be utilized in various industries, including construction, non-woven, furniture, carpet, agriculture, and paper. The alternative materials presented offer excellent mechanical, thermal, and acoustic properties, providing sustainable alternatives in applications ranging from civil construction to insulation and structure reinforcement, minimizing environmental impact. Green material alternatives enhance cost-effectiveness in constructing eco-friendly buildings, reducing the need for extracting new raw materials and minimizing the carbon footprint. It is expected that research on opportunities for recovering textile waste will soon intensify, leading to the implementation of these new eco-friendly products.